Analisis D-loop DNA Mitokondria untuk Memposisikan Ayam Hutan Merah dalam Domestikasi Ayam di Indonesia - S Sulandari; M.S A Zein (Media Peternakan, 2009)
The current poultry is a domesticated chickens used for both meat and egg production. Pedigree investigation is an important part to understand the process of chicken domestication in Indonesia. Molecular DNA approach using D-loop Mitochondrial DNA marker (hypervariable 1 segment) was used in this analysis. The objective of the study was to construct the pedigree analysis of Indonesian chicken. Four hundreds and eighty four (434) samples belonging to 15 breeds of Indonesian local chicken (Cemani, Kedu, Kedu Putih, Pelung, Sentul, Wareng, Merawang, Kapas, Kate, Arab Silver, Arab Gold, Gaok, Nunukan, Kalosi and Tolaki) and 9 samples of Red jungle fowls (Gallus gallus gallus) were extracted, PCR amplified and subsequently sequenced. Four sequence references from GeneBank, Gallus gallus (NCBI, accession number AB0986688). G. gallus (GenBank accession number AB098668), G. gallus spadiceus (GenBank accession number AB007721), and G. gallus bankiva (GenBank accession number AB007718) were included in this analysis. The sequences of the first 397 nucleotides were used for analysis. The results show that 72 haplotypes were identified from 56 polymorphic sites. Phylogenetic analysis showed that Indonesian chicken have a close relationship with 2 subspecies of Gallus gallus (G. gallus gallus and G. gallus spadiceus). Our results suggest that D-loop region is highly variable in Indonesian chicken with large number of haplotypes. Key words: Gallus gallus, Indonesian chicken, D-loop Mitochondrial DNA